Impacts that the pandemic has caused on the elective surgery process: a bibliographic review (Research, Society and Development, 2022)
Covid-19, with the genesis of acute infection, is high infection by the SARS-CoV2 virus, which has a transmissibility rate and high infection. In this context, the growing demand of contaminated patients made it possible to carry out other types of treatments. Research points to a large drop in elective surgeries in time of a pandemic. Therefore, the objective of this research is to find out what impacts the COVID-19 pandemic had on elective surgeries, since they were marked by the advancement and spread of the virus. In this way, a literature review methodology research on articles that discuss a topic addressed between the years 2020 and 2022, as they were published in the PubMed and Scielo databases. The COVID-19 pandemic promotes changes in medical and hospital protocols around the world resulting, including, without cancellation of surgeries, punctuating great impacts, even on the survival of some patients. In this way, the way patients were needed, how patients and patients did not use the possible procedures for patients and medical equipment, as well as testing on all patients and professional equipment. Proposals that were timed to meet requests for graded surveys of elective surgeries, than those that were not detected by the COVID-19 determination were verified by the procedures. It is important that this gradual return prioritize those patients who need it the most, according to the degrees of complexity for the surgery to be performed.